2007
DOI: 10.1021/la700597k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stabilization of Emulsions Due to Surfactant-Induced Nanoparticle Flocculation

Abstract: We have shown recently (Binks, B. P.; Rodrigues, J. A.; Frith, W. J. Langmuir 2007, 23, 3626) that, for mixtures of negatively charged silica nanoparticles and cationic surfactant, oil-in-water emulsions are most stable to creaming and coalescence at conditions of maximum flocculation of particles by surfactant in aqueous dispersions alone. Here, we extend the idea using positively charged silica particles in mixtures with anionic surfactant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
184
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 237 publications
(193 citation statements)
references
References 19 publications
9
184
0
Order By: Relevance
“…This strategy of in situ surface modifi cation affords fl exibility in the selection of colloids lacking in the traditional bijel fabrication route. [24][25][26][27][28] Bijels, for example, can be prepared with positively charged silica nanoparticles modifi ed in situ with an anionic surfactant (Figure 1 a).…”
Section: Doi: 101002/adma201503509mentioning
confidence: 99%
“…This strategy of in situ surface modifi cation affords fl exibility in the selection of colloids lacking in the traditional bijel fabrication route. [24][25][26][27][28] Bijels, for example, can be prepared with positively charged silica nanoparticles modifi ed in situ with an anionic surfactant (Figure 1 a).…”
Section: Doi: 101002/adma201503509mentioning
confidence: 99%
“…In contrast to silica nanoparticles, alumina nanoparticles are positively charged in neutral water, 48,49 and there is no direct interaction between them and the CO 2 /N 2 switchable surfactants. On the other hand it is possible to hydrophobize in situ these nanoparticles using anionic amphiphiles such as anionic surfactant, 48 short chain fatty acids 50 and functional polymers 51 to endow them with surface activity.…”
Section: -47mentioning
confidence: 99%
“…On the other hand it is possible to hydrophobize in situ these nanoparticles using anionic amphiphiles such as anionic surfactant, 48 short chain fatty acids 50 and functional polymers 51 to endow them with surface activity. In this paper we report on CO 2 /N 2 triggered switchable Pickering emulsions prepared by using positively charged nanoparticles in combination with the anionic surfactant sodium dodecyl sulfate (SDS) and equal moles of the switchable surfactant N 0 -dodecyl-N,N-dimethylacetamidine (DDAA).…”
Section: -47mentioning
confidence: 99%
“…Recently, much attention has been paid to the use of solid particles combined with various surfactants in Pickering emulsion [2][3][4][5][6][7][8][9][10][11][12][13][14]. For example, Binks and co-workers prepared oil-in-water Pickering emulsion with surface-active silica particle and cationic surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Binks and co-workers prepared oil-in-water Pickering emulsion with surface-active silica particle and cationic surfactant. The synergism between silica particles and surfactant led to greatly enhanced stability of the resultant Pickering emulsions, and the emulsions were most stable under conditions where particles were most flocculated [3,9]. Recently, Worthen reported that the synergism between silica nanoparticles and a weakly interacting zwitterionic surfactant also resulted in a greater stability to coalescence compared to the emulsion with either nanoparticles or surfactant alone [11].…”
Section: Introductionmentioning
confidence: 99%